Desain Konsep Inovasi Perahu Wisata Panorama Bawah Air Lobang Buaya, Pantai Namanalu-Negeri Morella - Siahainenia, Reico H. (Industrial Engineering Study Program, Pattimura University, 2025)
Tourists who enjoy the panoramic beauty of the underwater Namanalu beach,